THE COLLABORATIVE AGING RESEARCH USING TECHNOLOGY (CART) INITIATIVE: DIVERSE COHORTS - Silbert, L (Innov Aging, 2018)
The CART initiative emphasizes real-world scalability and addressing the needs of diverse populations. To this end, the project is enrolling volunteers (couples and those living alone) to participate in the initiative consenting to have the CART suite of technologies installed in their home while relevant clinical data is collected informing primarily the degree to which key functional abilities and health and wellness traits are captured. Four sites represent key constituencies that have not previously been widely included in pervasive computing research including older adults: 1) of low-income (living in section 202 housing in Portland, Oregon); 2) who are African Americans (participating in the Minority Aging Research Study in Chicago); 3) of Spanish-speaking heritage (in Miami, Florida); and 4) rural-residing veterans (living in the northwest Veterans Service Network area 20). The presentation will review enrollments to date focusing on the process of enrollment and preliminary experience with the CART system.